Marine Conservation and Traditional Ecology in Journal Articles: A Readability and Relevance Study for Academic Reading Learning in Higher Education - Pujiastuti Indah; Lestari Dian; Damayanti Vismaia S.; Mulyati Yeti; Sastromihardjo Andoyo (SHS Web of Conferences)
This study aims to evaluate the relevance and readability of journal articles on the theme of marine conservation and traditional ecology so that they can be used as teaching materials in learning to read academic texts in universities. The data collection method used Systematic Literature Review (SLR) with article sources from Google Scholar through Publish or Perish 8 metadata collection software. The articles chosen in this research are journal articles determined in the period 2019-2024. Of the 500 articles identified, ten (10) articles were selected based on the criteria of theme relevance, readability, and journal accreditation, as well as the use of Indonesian. The articles were evaluated using qualitative content analysis techniques, with a focus on exploring the themes of marine conservation and the application of local wisdom, as well as readability analysis using Fry's graph test to ensure the texts were appropriate for students' reading ability. The results show that the selected articles can be used as teaching materials for academic reading, although adjustments are needed in terms of effective sentences and grammar. The articles also provide a deeper understanding of the importance of traditional ecology in preserving marine ecosystems and its relevance in academic reading learning at the tertiary level.